Framing Interpersonal Kyai Dalam Peningkatan Reputasi Pondok Pesantren Nurul Qadim - Moh. Samsul Bahri (CV Edujavare Publishing, 2023)
Islamic boarding schools are religious educational institutions that are characteristic of Indonesia. Kiai as the highest leader in the Islamic boarding school is expected to be able to increase the reputation of the Islamic boarding school that has been nurtured. The purpose of this study was to determine Kiai's framing in improving Nurul Qodim Islamic boarding school. The method used in this study is qualitative (Naturalistic) obtained from several resource persons, Data collection techniques in this study are carried out circularly using three methods, namely; 1) participant observation; 2) In-depth interviews. The results of this research Framing Interpersonal Kyai can improve the reputation of Islamic boarding schools with the following steps: explore content dimensions related to the topics of passion, commitment, and closeness to describe the relationship dimensions related to dominance - submissiveness, affiliation-disaffiliation and procedural records of participants' speeches, highlighting human society and other positive activities both directly and on social media, Educating the community with easily digestible and correct contextualization, utilizing geopolitics, positive activities, and community reality at all economic levels, promoting rituals of smiles, greetings, and direct action when needed by the community, Seeking the growth of positive public attitudes and images towards institutions.